Meaningful, cognitive, and leisure activities and life satisfaction in community-dwelling older adults - Hasbullah, Mardhiyah; Dahlan, Akehsan (Universiti Teknologi Mara Cawangan Pulau Pinang, 2025)
Engagement in meaningful, cognitive, and leisure activities has been shown to influence life satisfaction among older adults. This study examined these relationships in a cross-sectional survey of 134 community-dwelling older adults aged 60 years and above. Instruments included the Engagement in Meaningful Activities Survey (EMAS-12), Satisfaction with Life Scale (SWLS-5), and Cognitive and Leisure Activities Scale (CLAS-16). Based on established scoring, EMAS engagement levels were categorised as low (<30), moderate (30–39), and high (≥40). Results indicated that 59% of participants reported moderate engagement, 26.1% high engagement, and 14.9% low engagement. Mean scores were EMAS 36.1 (SD = 7.44), SWLS 29.28 (SD = 3.77), and CLAS 40.41 (SD = 10.00). Correlation analysis revealed that EMAS was significantly associated with SWLS (r = 0.45, p < 0.001) and CLAS (r = 0.44, p < 0.001), while SWLS was also positively related to CLAS (r = 0.27, p = 0.002). Significant differences in engagement were found based on community activity involvement (p < 0.001), education level (p < 0.001), and occupation type (p < 0.001). A weak but significant negative correlation was observed between EMAS and age (r = –0.29, p < 0.001). These findings suggest that while life satisfaction among older adults was generally high, engagement in meaningful and cognitive-leisure activities was only moderate, highlighting the need for tailored, age-friendly interventions. This study addresses reviewer feedback by clarifying the cut-off points for engagement categories to enhance interpretability of results.